Impaired spatial dynamic functional network connectivity and neurophysiological correlates in functional hemiparesis - E. Premi; V. Cantoni; A. Benussi; A. Iraji; V.D. Calhoun; D. Corbo; R. Gasparotti; M. Tinazzi; B. Borroni; M. Magoni (NeuroImage: Clinical)
The present study investigated spatial dynamic functional network connectivity (dFNC) in patients with functional hemiparesis (i.e., functional stroke mimics, FSM). The aim of this work was to assess static functional connectivity (large-scale) networks and dynamic brain states, which represent distinct dFNC patterns that reoccur in time and across subjects. Resting-state fMRI data were collected from 15 patients with FSM (mean age = 42.3 ± 9.4, female = 80 %) and 52 age-matched healthy controls (HC, mean age = 42.1 ± 8.6, female = 73 %).Each patient underwent a resting-state functional MRI scan for spatial dFNC evaluation and transcranial magnetic stimulation protocols for indirect assessment of GABAergic and glutamatergic transmission. We considered three dynamic brain networks, i.e., the somatomotor network (SMN), the default mode network (DMN) and the salience network (SN), each summarized into four distinct recurring spatial configurations. Compared to HC, patients with FSM showed significant decreased dwell time, e.g. the time each individual spends in each spatial state of each network, in state 2 of the SMN (HC vs. FSM, 13.5 ± 27.1 vs. 1.9 ± 4.1, p = 0.044). Conversely, as compared to HC, FSM spent more time in state 1 of the DMN (10.8 ± 14.9 vs. 27.3 ± 38.9, p = 0.037) and in state 3 of the SN (23.1 ± 23.0 vs. 38.8 ± 38.2, p = 0.002). We found a significant correlation between the dwell time of impaired functional state of the SMN and measures of GABAergic neurotransmission (r = 0.581, p = 0.037). Specifically, longer impaired dwell time was associated with greater GABAergic inhibition. These findings demonstrate that FSM present altered functional brain network dynamics, which correlate with measures of GABAergic neurotransmission. Both dFNC and GABAergic neurotransmission may serve as potential targets for future intervention strategies.